Role of glutamate toxicity in neurodegeneration following traumatic brain injury in a human 3D in vitro brain-like tissue model - Shevzov-Zebrun, Anna (Tufts Archival Research Center, 2021)
Traumatic brain injury (TBI) is a prevalent cause of injury-related death, and in survivors often leads to long-term disrupted brain morphology and function. Glutamate toxicity is a previously identified cellular process associated with neuronal network degradation and cell death pathways, such as necroptosis, following TBI; however, the dependence of TBI on glutamate-induced damage and death pathways in humans remains unclear. In this study, a previously established human three-dimensional (3D) in vitro brain-like tissue model was used to investigate neuronal network degradation following controlled cortical impact (CCI), with and without treatments that ameliorate glutamate toxicity and the downstream effects. Following CCI, tissues demonstrated a gradual increase in cell stress markers and loss of neuronal network density, with complete loss of network structure by 72 hours. Riluzole, a glutamatergic drug with protective effects against TBI in animal models, failed to prevent TBI progression in this human 3D tissue model. Furthermore, after eliminating excess glutamate and reducing necroptotic activity with sodium pyruvate, neuronal network degradation continued at a similar rate to that of degradation in untreated injured tissues. In summary, our study used a novel 3D human neuronal system to explore TBI progression and indicated that glutamate toxicity may only be a downstream consequence of other injury-induced pathways.